Screening of mitochondrial mutations in Tunisian patients with mitochondrial disorders: An overview study. (June 2013) - Mkaouar-Rebai, Emna; Chamkha, Imen; Mezghani, Najla; Ayed, Imen Ben; Fakhfakh, Faiza
<x xml:space="preserve">Abstract</x> To investigate the spectrum of common mitochondrial mutations in Tunisia during the years of 2002–2012, 226 patients with mitochondrial disorders were clinically diagnosed with hearing loss, Leigh syndrome (LS), diabetes, cardiomyopathy, Kearns–Sayre syndrome (KSS), Pearson syndrome (PS), myopathy, mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes syndrome (MELAS) and Wolfram syndrome. Restriction fragment length polymorphism (PCR-RFLP), radioactive PCR, single specific primer-PCR (SSP-PCR) analysis and PCR-sequencing methods were used to identify the mutations. Two cases with m.1555A>G mutation and two families with the novel 12S rRNA m.735A>G transition were detected in patients with hearing loss. Three cases with m.8993T>G mutation, two patients with the novel m.5523T>G and m.5559A>G mutations in the tRNATrp gene, and two individuals with the undescribed m.9478T>C mutation in the cytochrome c oxidase subunit III (COXIII) gene were found with LS. In addition, one case with hypertrophic cardiomyopathy and deafness presented the ND1 m.3395A>G mutation and the tRNAIle m.4316A>G variation. Besides, multiple mitochondrial deletions were detected in patients with KSS, PS, and Wolfram syndrome. The m.14709T>C mutation in the tRNAGlu was reported in four maternally inherited diabetes and deafness patients and a novel tRNAVal m.1640A>G mutation was detected in a MELAS patient.